The role of reactive astrocitose in the chronological evolution of traumatic brain injury - Roxana M. Duncea-Borca; Vladimir Belis; Mihnea Costescu; Relu G. Calota; Reka Kutasi; Cosmin A. Moldovan (Journal of Mind and Medical Sciences)
Introduction and objectives. This study aims to investigate whether the cerebral modifications of posttraumatic reactive astrocitose can be considered an objective criterion for determining the age of traumatic cranio-cerebral lesions.